Associating frailty and dynamic dysregulation between motor and cardiac autonomic systems - Arrué, Patricio; Laksari, Kaveh; Russo, Mark; La Placa, Tana; Smith, Meghan; Toosizadeh, Nima (Frontiers in Aging, 2024)
Frailty is a geriatric syndrome associated with the lack of physiological reserve and consequent adverse outcomes (therapy complications and death) in older adults. Recent research has shown associations between heart rate (HR) dynamics (HR changes during physical activity) with frailty. The goal of the present study was to determine the effect of frailty on the interconnection between motor and cardiac systems during a localized upper-extremity function (UEF) test. Fifty-six individuals aged 65 or above were recruited and performed the previously developed UEF test consisting of 20-second rapid elbow flexion with the right arm. Frailty was assessed using the Fried phenotype. Wearable gyroscopes and electrocardiography were used to measure motor function and HR dynamics. In this study, the interconnection between motor (angular displacement) and cardiac (HR) performance was assessed, using convergent cross-mapping (CCM). A significantly weaker interconnection was observed among prefrail and frail participants compared to non-frail individuals (p<0.01, effect size=0.81±0.08). Using logistic models, pre-frailty and frailty were identified with sensitivity and specificity of 82% to 89%, using motor, HR dynamics, and interconnection parameters. Findings suggested a strong association between cardiacmotor interconnection and frailty. Adding CCM parameters in a multimodal model may provide a promising measure of frailty.